Pandangan Etika Kristen tentang Berbusana bagi Wanita Kristen - Evi Prasti (Sekolah Tinggi Teologi Berita Hidup, 2019)
In dressed placement there are special situations that require the wearer to dress in formal situations, namely government agencies, schools, offices and worship. In a semi-formal or causal situation that is a semi-formal situation but there is a limit of politeness also in non-formal situations such as in the market, at home. This situation has no rules that bind it from the three situations we must be able to choose clothing according to the provisions of the event we are going to attend. Christian women's clothing must be different, because it manifests the person of the Lord Jesus the Great and holy so that the appearance of dressed in Christianity especially prioritizes God rather than appearance. Because God is holy and holy, in practice daily life glorifies God through our bodies. In a position as a student, the clothes that are used are dress that is polite, not sexy, does not wear a T-shirt, does not wear a tight shirt, mini skirt, transparent clothes but can choose clothes that are reasonable and appropriate in the campus situation. AbstrakDalam penempatan berbusana ada situasi khusus yang menuntut si pemakai berbusana sapan dalam situasi formal yaitu instansi pemerintahan, sekolah, kantor dan beribadah. Dalam situasi semi formal atau causal yaitu situasi setengah formal tetapi ada batas kesopanan juga dalam situasi non formal seperti di pasar, dirumah. Situasi ini tidak ada peraturan yang mengikatnya dari ketiga situasi tersebut kita harus dapat memilih busana sesuai ketentuan acara yang kita akan hadiri. Busana wanita Kristen harus berbeda, karena mewujudkan pribadi Tuhan Yesus yang Agung dan kudus sehingga penampilan dalam berbusana orang Kristen terlebih mengutamakan Tuhan dari pada penampilan. Sebab tuhan adalah suci dan kudus maka dalam praktek kehidupan sehari hari memuliakan Tuhan melalui tubuh kita. Dalam posisi sebagai mahasiswa maka busana yang dipakai adalah busana yang sopan, tidak seksi, tidak memakai kaos oblong,tidak memakai kaos ketat,rok mini, baju transparan melainkan dapat memilih busana yang wajar dan pantas dalam situasi kampus.